The Islamization Of The Sciences: Its Philosophy And Methodology (American Journal of Islam and Society, 1987)
IntroductionThe idea of Islamizing the sciences, whether they be natural or social,raises some philosophical and methodological questions which must, in myview, be settled before any serious program of Islamization can be carried out.I shall, in this paper, do no more than give examples of these fundamentalquestions, give brief answers to some of them and throw out hints as tohow others can be answered. In doing so I shall do my best to keep as closeas possible to the Qur’an and the Sunnah, but I cannot claim that whateveranswers I give are the Islamic answers to the questions I raise.Philosophical QuestionsWhat does it mean to Islamize knowledge?The elucidation of this question and the answer to it are given in the followingimaginary dialogue between a Western philosopher, call him W, and aMuslim propounder of the Islamization of knowledge, call him M.W: Is Islam compatible with all forms of truth?M: Certainly.W Would you agree that if something is known, then it is true, i.e. thatknowledge implies truth?M: I agree provided that you make a distinction between knowledge andclaims to knowledge and provided that you agree that there are degrees of truth.W I accept the qualifications, but if knowledge implies truth, and truth inall its forms is compatible with Islam, then knowledge in all its forms is Islamic.But if this is so, what does it mean then to Islamize knowledge? How do youmake something Islamic which is already so? Or is it your intention merelyto give each form of knowledge an Islamic flavour by injecting an ayat here,imposing a hadith there, making an opening with bismillahi-rrahmani-rrahimand a closing with alhamdu lillahi rabbi-l'alamin? ...